Grammaticality vs. Acceptability. Issues in the EFL and ESP classroom - Naumoska, Aneta; Naumoska Sarakinska, Biljana (Universitatea Ovidius din Constanta, Romania, 2024)
Though the concepts of grammaticality and acceptability are obviously different, they are intrinsically linked where language is concerned, and especially in terms of (foreign) language learning. As such, grammaticality is more theoretical in nature, in connection to whether the grammatical rules of the language have been followed, that is, conformed to. Acceptability, on the other hand, has more to do with whether the language has been used appropriately in a particular situation and/or context, and in that sense, it is speaker-oriented. Bearing in mind the lingua franca status of English on the global stage, it is not unexpected that variations will occur in terms of what is deemed (un)acceptable through the prism of grammaticality, as well as through the prism of the approach employed - descriptive or prescriptive. This paper will take a closer look at the two concepts - grammaticality and acceptability - and compare them in terms of their similarities and differences, as well as look at their role in foreign language learning, focusing on the EFL and ESP classroom, the various challenges that might surface and the potential ways to deal with them. Bearing in mind that the primary purpose of language is to facilitate communication, we may conclude that this applies to foreign language learning, too, and in that context, it would be useful to take a closer look at which of the two notions holds greater significance in achieving communicative competence, whether they can work together for this aim, and if so, the strategies and techniques that may be employed.
Keywords: grammaticality, acceptability, EFL, ESP, prescriptive vs descriptive approach